IMPORTANCE OF INTEGRATING INTERCULTURAL COMPETENCE INTO ENGLISH LANGUAGE TEACHING - Arzieva, B.A. (SCIENCE and SOCIETY, 2024)
The article deals with the integrating intercultural competence into English language teaching based on the implementation of the linguistic and cultural approach. This article can be based on practical tips for teachers who want to integrate culture seamlessly into their language lessons by using technology for immersive cultural experiences creates inclusive and efficient language learning environments, empowering students to communicate confidently across cultures.
Keywords: intercultural interaction; the manifestation of tolerance; racial; national; religious tolerance; language stereotypes; cultural misunderstandings